2019
DOI: 10.3906/sag-1812-137
|View full text |Cite
|
Sign up to set email alerts
|

Importance of 14-3-3eta, anti-CarP, and anti-Sa in the diagnosis of seronegative rheumatoid arthritis

Abstract: Background/aim: Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation. The study aimed to assess serum 14-3-3eta, anti-CarP, and anti-Sa in seronegative RA (SNRA) patients who were treatment-naïve as well as in healthy subjects. This is the first study in the literature to examine these autoantibodies together in SNRA patients. Materials and methods: Forty-five treatment-naïve SNRA patients and 45 healthy subjects were recruited. Drugs change the levels of autoantibodies; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Next, we carried out the subgroup analysis by Meta‐Disc 1.4 based on gender ratio, mean age, ethnicity, case number of RA patients, control groups, and study design. As shown in Table , after grouping, both the inconsistency (1‐square) of pooled sensitivity and specificity decreased in African and European groups, in Asian populations, 15,17,24‐26,28,29 the pooled sensitivity had no apparent change (0.73 [0.71‐0.75]) and the pooled specificity increased (0.91 [0.89‐0.93]); in African populations, 18,27,30 both the pooled sensitivity (0.88 [0.82‐0.93]) and specificity (0.91 [0.85‐0.95]) augmented; however, in European groups, 16,31,32 the pooled sensitivity (0.67 [0.63‐0.71]) and specificity (0.83 [0.80‐0.86]) declined. As shown in Table , in healthy and disease control, 16‐18,25,26,28‐32 the diagnostic value of pooled sensitivity decreased to 0.67 (0.65‐0.70) and pooled specificity had no apparent change (0.88 [0.86‐0.90]); however, in healthy controls, 15,24,27 both the pooled sensitivity (0.96 [0.93‐0.98]) and specificity (0.90 [0.84‐0.95]) increased, and both the inconsistency (1‐square) of pooled sensitivity and specificity decreased.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Next, we carried out the subgroup analysis by Meta‐Disc 1.4 based on gender ratio, mean age, ethnicity, case number of RA patients, control groups, and study design. As shown in Table , after grouping, both the inconsistency (1‐square) of pooled sensitivity and specificity decreased in African and European groups, in Asian populations, 15,17,24‐26,28,29 the pooled sensitivity had no apparent change (0.73 [0.71‐0.75]) and the pooled specificity increased (0.91 [0.89‐0.93]); in African populations, 18,27,30 both the pooled sensitivity (0.88 [0.82‐0.93]) and specificity (0.91 [0.85‐0.95]) augmented; however, in European groups, 16,31,32 the pooled sensitivity (0.67 [0.63‐0.71]) and specificity (0.83 [0.80‐0.86]) declined. As shown in Table , in healthy and disease control, 16‐18,25,26,28‐32 the diagnostic value of pooled sensitivity decreased to 0.67 (0.65‐0.70) and pooled specificity had no apparent change (0.88 [0.86‐0.90]); however, in healthy controls, 15,24,27 both the pooled sensitivity (0.96 [0.93‐0.98]) and specificity (0.90 [0.84‐0.95]) increased, and both the inconsistency (1‐square) of pooled sensitivity and specificity decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Salman et al found that 40 (88%) of their 45 patients who were seronegative for RF and ACPA were 14-3-3η-positive and suggested that 14-3-3η protein is a valuable and promising marker in patients with SNRA. 24 Another of the advantages of 14-3-3 η protein as an RA marker is that adding 14-3-3 η to RF or ACPA or the combination of all 3 markers would increase the diagnostic rate. Guan et al found that adding 14-3-3 η to RF and ACPA testing increased diagnostic sensitivity for early RA patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations